2003
DOI: 10.2176/nmc.43.383
|View full text |Cite
|
Sign up to set email alerts
|

Intraorbital Mucocele Associated With Old Minor Trauma-Case Report-

Abstract: A 46-year-old white man complained of swelling in the left orbital region. The only significant event in his medical history was minor trauma which occurred during ice hockey 15 years previously. On admission, the only clinical finding was left-sided exophthalmos. Computed tomography and magnetic resonance imaging revealed a left intraorbital cystic mass lesion. The cystic mass was completely removed through a left subfrontal extradural approach. There was no anatomical contact with the paranasal sinuses and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Radiologically, mucocele has typical characteristics, but often nonspecific depending on the amount of its protein content or superinfection 1,3 . Considering the pathophysiology of the isolated orbital mucoceles differs, and there is no communication with the paranasal sinuses, some authors suggest that treatment requires complete excision or destruction of the ectopic sinus tissue within the orbit by external approaches 1,2,5,6 . However, these external approaches have many disadvantages, including eyelid or upper lip scar, ectropion or entropion of the eyelid, periorbital swelling and pain, diplopia, prolonged operation time, and healing time 5,7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiologically, mucocele has typical characteristics, but often nonspecific depending on the amount of its protein content or superinfection 1,3 . Considering the pathophysiology of the isolated orbital mucoceles differs, and there is no communication with the paranasal sinuses, some authors suggest that treatment requires complete excision or destruction of the ectopic sinus tissue within the orbit by external approaches 1,2,5,6 . However, these external approaches have many disadvantages, including eyelid or upper lip scar, ectropion or entropion of the eyelid, periorbital swelling and pain, diplopia, prolonged operation time, and healing time 5,7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Isolated intraorbital mucocele without anatomical communication between the sinus and orbital cavity, and all orbital walls are intact is rare 1 . Causes of mucocele are trauma, inflammation, mass lesions such as polyps and osteosis, or anatomic anomalies which may lead to sinus obstruction 2 . Mucocele is typically seen as a cystic mass with non-contrast enhanced soft tissue density and clear margin in computed tomography (CT) 1,3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 55-year-old man was diagnosed with left isolated orbital mucocele without a history of trauma or obstruction of paranasal sinus. Asamoto et al reported an isolated orbital mucocele from old fracture of 46-year-old man with significant history of minor trauma over the nose happened during ice hockey 6 . He suggested that orbital mucocele was caused by aberration of sinus mucosa into orbital cavity during trauma.…”
Section: Discussionmentioning
confidence: 99%
“…mesenchymale Chondrosarkome [61], vaskuläre Malformationen [62,63], benigne chondroide Syringome [64], Ewing-Sarkome [65], Schwannome [66], Plasmozytome [67], Mukozelen [68], akute lymphoblastische Leukämie [69] und Tumoren der Tränendrüse wie adenoidzystisches Karzinome [70] und Onkozytome [71]. Darüber hinaus können systemische Erkrankungen wie Tuberkulose [72,73] und Sarkoidose [74] potenziell die Orbitae betreffen.…”
Section: Diskussionunclassified